TEKNOLOGI, MOTIVASI BELAJAR DAN PENGEMBANGANNYA DALAM PENDIDIKAN ISLAM - Murjani Murjani (ADIBA : JOURNAL OF EDUCATION, 2022)
Characteristics of Motivation in Learning; Interested in the teacher, which means not hating or being indifferent, Interested in the subject being taught, Has high enthusiasm and controls his attention especially to the teacher, Wants to always join the class group, Wants his identity to be recognized by others, Actions, habits and morals always in self-control, Always remembering lessons and relearning them; and always controlled by the environment.